The novel subclusters based on cancer-associated fibroblast for pancreatic adenocarcinoma - Zhao, Guojie; Wang, Changjing; Jiao, Jian; Zhang, Wei; Yang, Hongwei (Frontiers in Oncology, 2022)
Background Pancreatic adenocarcinoma (PAAD) is a fatal disease characterized by promoting connective tissue proliferation in the stroma. Activated cancer-associated fibroblasts (CAFs) play a key role in fibrogenesis in PAAD. CAF-based tumor typing of PAAD has not been explored. Methods We extracted single-cell sequence transcriptomic data from GSE154778 and CRA001160 datasets from GEO or Tumor Immune Single-cell Hub (TISCH) to collect cancer-associated fibroblast (CAF) in PAAD. Based on Seurat packages and new algorithms in machining learning, CAF-related subtypes and their top genes for PAAD were analyzed and visualized. We used CellChat package to perform Cell-cell communication analysis. In addition, we carried out functional enrichment analysis based on clusterProfiler package. Finally, we explored the prognostic and immunotherapeutic value of these CAF-related subtypes for PAAD. Results CAFs were divided into five new subclusters (CAF-C0, CAF-C1, CAF-C2, CAF-C3 and CAF-C4) based on their marker genes. The five CAFs subclusters exhibited distinct signaling patterns, immune status, metabolism features, and enrichment pathways, and validated in he pancancer datasets. In addition, we found that both CAF-C2 and CAF-C4 subgroups were negatively correlated with prognosis. With their top genes of each sub clusters, the subCAF2 had significantly relations to immunotherapy response in the patients with pan-cancer and immunotherapy. Conclusion We explored the heterogeneity of five subclusters based on CAF in signaling patterns, immune status, metabolism features, enrichment pathways and prognosis for PAAD.